RESILIENSI DAN QUARTER LIFE-CRISIS PADA MAHASISWA TINGKAT AKHIR - Sallata, Jean Michelle Madeline; Huwae, Arthur (Jurnal Cakrawala Ilmiah, 2023)
One of the events that arise during the transition between adolescence and adulthood is a quarter-life crisis, which is a feeling of worry in a person caused by the uncertainty of future life. To overcome a quarter-life life crisis, resilience is needed to overcome the problems and difficulties faced. This study aims to determine the relationship between resilience and quarter-life crisis in final-year students. The method used was a quantitative correlational design. A total of 113 participants were obtained using an accidental sampling technique. Measurements used the Resilience Quotient Test and the Quarter Life-Crisis Scale. The data analysis method uses the Pearson Correlation correlation test. The results showed a significant negative relationship between resilience and quarter-life crisis in final-year students (r = 0.346 and significance 0.000). This indicates that resilience is one of the factors associated with increasing or decreasing quarter-life crises in final-year students